Kombinasi Metode Webqual 4.0 dan Importance Performance Analysis pada Pengukuran Kualitas Website Stock Exchange - Rakhmadani, Diovianto Putra; Nabila, Viryal (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Interest in stock investment in Indonesia is still relatively low compared to other countries, data shows that the population of productive age has reached 189 million, but there are only 4.16 million retail investors in the capital market with an involvement ratio of around 2.2 percent. This shows that the participation ratio of the Indonesian population in investing in shares is less than 5 percent, which is far behind other countries such as the United States (55 percent), Singapore (26 percent) and Malaysia (9 percent). The lagging interest in investing is due to a lack of understanding of digital literacy in investing. This needs to be overcome by increasing the digital literacy understanding of the Indonesian people regarding investing in shares. The webqual 4.0 method is a method used to measure the quality of the stock exchange information system website in Indonesia, namely IDX.co.id, through the use of three measurement variables, namely in terms of usability, information quality, service interaction quality. In addition, the Importance Performance Analysis (IPA) method is applied to carry out performance assessments on expectations of website quality. It can be measured to identify indicators according to user preferences, then the results of these measurements are used to identify indicators that need to be improved on the IDX information system so that can improve user experience, as well as increase digital literacy of stock investment in Indonesia. This research collects information from users through questionnaires which are processed using the linear regression analysis method. The research results show that users are satisfied with the current IDX Website in terms of Usability, Information Quality and Service Interaction Quality, indicated by the T-Statistics value which is higher than the T-Table. So that the public's understanding of digital stock investing literacy facilitated by the idx.co.id website is good. However, based on the Importance Performance Analysis analysis, improvements still need to be made to indicators in quadrants I and III which have low performance. Recommended improvements include improving site navigation, implementing SEO, site redesign, increasing credibility, reorganizing menus, content audits, and increasing user interaction.